Direct pulmonary delivery route in lung cancer: a highway for siRNA therapeutics - Sharif, Muhammad Shakeeb; Luzzi, Luca; De Laurentiis, Michelino; Giordano, Antonio; Barbarino, Marcella (Frontiers in Oncology, 2026)
Direct drug delivery encompasses minimally invasive methods for the local administration of therapeutics and is already widely applied in diseases affecting the liver, eyes, peritoneum, breast, joints, coronary arteries, and brain. In oncology, localized approaches such as intratumoral injections, implantable depots, inhalable aerosols, and image-guided procedures allow controlled drug release at tumor sites with high selectivity. Given its large surface area, rich vascularization, and anatomical accessibility, the respiratory system provides an ideal setting for direct delivery strategies across a range of respiratory diseases. Among these, lung cancer, the leading cause of cancer-related deaths worldwide, is characterized by high molecular heterogeneity, making it particularly suitable for targeted gene-silencing and replacement therapies at specific oncogenic drivers. Advances in genomics and transcriptomics increasingly support the potential of gene therapy, especially RNA-based therapeutics and gene-editing technologies, to selectively silence or correct oncogenic mutations. In patients with unresectable or recurrent disease, where therapeutic precision is crucial, the combination of direct pulmonary drug delivery and RNA-based therapies offers a powerful synergy: anatomical precision, reduced systemic toxicity, and molecular selectivity targeting tumor-specific alterations. Unlike previous reviews, this work provides an integrated perspective that bridges findings from orthotopic in vivo studies on siRNA nanomedicine with emerging clinical evidence, underscoring direct pulmonary delivery as a central strategy in precision medicine for lung cancer. By critically examining advanced delivery technologies, the review considers both their potential advantages and the scientific and technical challenges that remain in the clinical translation of siRNA for lung cancer. Moreover, by highlighting how direct pulmonary administration can overcome these challenges, it underscores the transformative potential of siRNA therapeutics in lung cancer and the need for sustained, high-intensity collaboration between scientists and clinicians to advance RNA-based therapies in thoracic oncology.